Propensity score–based comparison of the graft failure risk between kidney transplant recipients of standard and expanded criteria donor grafts: Toward increasing the pool of marginal donors. Issue 5 (8th February 2018) - Querard, A. H.; Le Borgne, F.; Dion, A.; Giral, M.; Mourad, G.; Garrigue, V.; Rostaing, L.; Kamar, N.; Loupy, A.; Legendre, C.; Morelon, E.; Buron, F.; et al.
Abstract : From a prospective and multicentric French cohort, we proposed an external validation study for the expanded criteria donor (ECD), based on 4833 kidney recipients transplanted for the first time between 2000 and 2014. We estimated the subject‐specific effect from a multivariable Cox model. We confirmed a 1.75‐fold (95% confidence interval [CI] 1.53‐2.00, P  < .0001) increase in graft failure risk if a given patient received an ECD graft compared to a graft from a donor with standard criteria (standard criteria donor [SCD]). Complementarily, we estimated the population‐average effect using propensity scores. We estimated a 1.34‐fold (95% CI 1.09‐1.64, P  = .0049) increase in graft failure risk among ECD patients receiving an ECD graft compared to receiving a SCD graft. With a 10‐year follow‐up, it corresponded to a decrease of 8 months of the mean time to graft failure due to ECD transplantation (95% CI 2‐14 months). The population‐average relative risk due to ECD transplantation and the corresponding absolute effect seem finally not so high. Regarding the increase of quality of life in transplantation, our study constitutes an argument to extend the definition of marginality by considering more grafts at high risk and thereby enlarging the pool of kidney grafts. Abstract : In a comparison of the risk of graft failure between kidney transplant recipients of a standard or an expanded criteria donor, this study finds a difference in risk of 13% at 10 years posttransplantation, which is an argument in favor of extending the definition of marginality criteria. See Englesbe's editorial onpage 1043 .